A New Laparoscopic Surgical Procedure to Achieve Sufficient Mesorectal Excision in Upper Rectal Cancer. (20th October 2011) - Ohigashi, Seiji; Taketa, Takashi; Sudo, Kazuki; Shiozaki, Hironori; Onodera, Hisashi
Abstract : Objective . Mesorectal excision corresponding to the location of a tumor, termed tumor-specific mesorectal excision (TSME), is commonly performed for resection of upper rectal cancer. We devised a new laparoscopic procedure for sufficient TSME with rectal transection followed by mesorectal excision. Operative Technique . After mobilization of the sigmoid colon and ligation of inferior mesenteric vessels, we dissected the mesorectum along the layer of the planned total mesorectal excision. The rectal wall was carefully separated from the mesorectum at the appropriate anal side from the tumor. After the rectum was isolated and transected using an endoscopic linear stapler, the rectal stump drew immediately toward the anal side, enabling the mesorectum to be identified clearly. In this way, sufficient TSME can be performed easily and accurately. This technique has been successfully conducted on 19 patients. Conclusion . This laparoscopic technique is a feasible and reliable procedure for achieving sufficient TSME.